Knowledge and Role of Cadres in Early Detection Stunting in Toddlers: Pengetahuan dan Peran Kader dalam Deteksi Dini Stunting pada Balita - Siregar, Nilda Yulita; Hakim, Fitrayani; Ramadhan, Kadar (Napande: Jurnal Bidan, 2023)
Background: Stunting is a condition of failure to thrive in children under five due to chronic malnutrition. Indonesia has a fairly high prevalence of stunting. The role of Posyandu cadres in preventing stunting through monitoring toddler growth requires knowledge so that they are good at early detection of stunting. Objective: knowledge and role of cadres in early detection of toddler stunting. Method: Descriptive research was conducted in the Lawanga Community Health Center Working Area from April to July 2020. The population of all cadres in the Lawanga Community Health Center Working Area with a sample of 35 people used simple random sampling. Results: There are 4 cadres with good knowledge and a role in early detection of stunting (100%). Cadres have sufficient knowledge and play a role in early detection of stunting, numbering 7 people (77.8%). There are 21 cadres who lack knowledge and play a role in early detection of stunting (95.5%). Conclusion: The role of cadres with less knowledge is greatest in early detection of stunting in toddlers. It is recommended that community health centers provide more information and motivation to cadres to take part in stunting early detection training programs.